A STUDY OF THE COMPARATIVE IMPACT OF CO-CURRICULAR ACTIVITIES ON SOCIAL SKILLS AND EMOTIONAL MATURITY OF STUDENTS STUDYING IN GOVERNMENT AND NON-GOVERNMENT SCHOOLS - Jha, Pragya; Dewangan, Savita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The objective of this comparative study is to compare the impact of co-curricular activities on social skills and emotional maturity among Grade 10 students studying in government and non-government schools in Durg district, Chhattisgarh. 600 students (305 students in government schools; 295 students in non-government schools) were selected from 20 schools (10 government schools, 10 private schools) using simple random sampling. The Social Skills Rating Scale (SSR; Sood, Anand & Kumar) was used for social skills, and the Emotional Maturity Scale (EMS; Tara Sabpati) was used for emotional maturity. Data were analyzed using descriptive statistics, independent-sample t-tests, and one-factor ANOVA. Key findings include: (i) the difference between government and private schools on overall social skills was nonsignificant; (ii) non-government students had higher average scores on overall emotional maturity (p<.01). (iii) gender-based patterns are complex—government schools excelled on some dimensions of social skills among male students, while differences by institution type were small/nonsignificant among female students. The study indicates that while a resource-rich environment promotes emotional maturity, the development of social skills is more dependent on institutional culture, opportunity structures, and participation patterns. At the policy level, strengthening SEL/counseling in government schools and expanding inclusive/community-engagement programs in private schools would be beneficial.